HMGB1 facilitates repair of mitochondrial DNA damage and extends the lifespan of mutant ataxin‐1 knock‐in mice. Issue 1 (15th December 2014) - Ito, Hikaru; Fujita, Kyota; Tagawa, Kazuhiko; Chen, Xigui; Homma, Hidenori; Sasabe, Toshikazu; Shimizu, Jun; Shimizu, Shigeomi; Tamura, Takuya; Muramatsu, Shin‐ichi; Okazawa, Hitoshi
Abstract Mutant ataxin‐1 (Atxn1), which causes spinocerebellar ataxia type 1 (SCA1), binds to and impairs the function of high‐mobility group box 1 (HMGB1), a crucial nuclear protein that regulates DNA architectural changes essential for DNA damage repair and transcription. In this study, we established that transgenic or virus vector‐mediated complementation with HMGB1 ameliorates motor dysfunction and prolongs lifespan in mutant Atxn1 knock‐in (Atxn1‐KI) mice. We identified mitochondrial DNA damage repair by HMGB1 as a novel molecular basis for this effect, in addition to the mechanisms already associated with HMGB1 function, such as nuclear DNA damage repair and nuclear transcription. The dysfunction and the improvement of mitochondrial DNA damage repair functions are tightly associated with the exacerbation and rescue, respectively, of symptoms, supporting the involvement of mitochondrial DNA quality control by HMGB1 in SCA1 pathology. Moreover, we show that the rescue of Purkinje cell dendrites and dendritic spines by HMGB1 could be downstream effects. Although extracellular HMGB1 triggers inflammation mediated by Toll‐like receptor and receptor for advanced glycation end products, upregulation of intracellular HMGB1 does not induce such side effects. Thus, viral delivery of HMGB1 is a candidate approach by which to modify the disease progression of SCA1 even after the onset.